2017
DOI: 10.2147/jpr.s139324
|View full text |Cite
|
Sign up to set email alerts
|

Application of the chronic constriction injury of the partial sciatic nerve model to assess acupuncture analgesia

Abstract: PurposeTo validate and explore the application of a rat model of chronic constriction injury to the partial sciatic nerve in investigation of acupuncture analgesia.MethodsChronic constriction injury of the sciatic nerve (CCI) and chronic constriction injury of the partial sciatic nerve (CCIp) models were generated by ligating either the sciatic nerve trunk or its branches in rats. Both models were evaluated via paw mechanical withdrawal latency (PMWL), paw mechanical withdrawal threshold (PMWT), nociceptive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The intensities of EA used in this study were identified as the thresholds of the A- and C-fiber activation. The ipsilateral biceps femoris muscle reflex was evoked by electrical stimulation of the A- and C-fibers within the receptive field of the sural nerve ( Guirimand et al, 1994 ; Zhi et al, 2017 ). Specifically, EMG responses were recorded via a pair of needles inserted into the biceps femoris muscle.…”
Section: Methodsmentioning
confidence: 99%
“…The intensities of EA used in this study were identified as the thresholds of the A- and C-fiber activation. The ipsilateral biceps femoris muscle reflex was evoked by electrical stimulation of the A- and C-fibers within the receptive field of the sural nerve ( Guirimand et al, 1994 ; Zhi et al, 2017 ). Specifically, EMG responses were recorded via a pair of needles inserted into the biceps femoris muscle.…”
Section: Methodsmentioning
confidence: 99%
“…Needling beyond and not at the site of compression is common in practice as most points being needled for sciatica are distal or proximal to sites of potential nerve compression. This approach has shown to inhibit nociception in CCI models of neuropathic pain lending support to the common acupuncture practices for sciatica [ 13 ]. For sciatica, placement of needles along the dermatomes, myotomes and spinal segments related to the sciatic nerve seems to be effective [ 52 ].…”
Section: Discussionmentioning
confidence: 96%
“…Due to their position, A1Rs have been shown to modulate Aβ fiber activity and reduce tactile allodynia under conditions of NP [ 20 ]. Adenosine also acts on A1Rs of afferent terminals to inhibit substance P (SP), calcitonin gene related peptide (CGRP) and excitatory neurotransmitter release [ 100 ] making it useful for NP by counteracting increased neuropeptide expression that occurs following nerve injury [ 13 ]. Evidenced demonstrates that ectonucleotidases reside within the epineurium of peripheral nerves, the membrane of DRG neurons and their axon terminals in lamina Ⅱ, which hydrolyze nucleotides into adenosine [ 95 , 96 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the present study was undertaken to examine the interaction of analgesic and anxiolytic effects of crocin with α1-and α2-adrenoceptors of ACC in chronic constriction injury (CCI) model of the sciatic nerve. It is shown that CCI model is an animal model of neuropathic pain, which is similar to human peripheral nerve injury and its sign and symptoms [28].…”
Section: Introductionmentioning
confidence: 99%